Impact of physical layer impairments on C+L-band metro networks - Gomes, F.; Cancela, L. G.; Rebola, J. L. (Proceedings of the 10th International Conference on Photonics, Optics and Laser Technology (PHOTOPTICS 2022), 2022)
To ensure future data traffic capacities, multi-band transmission in optical networks is being proposed, by adding wavelength division multiplexing channels in the L-band to the existing C-band channels. In this work, we study the filterless drop and waste amplified and unamplified solutions used in metro networks with L-band tributary nodes. The cost and power consumption of these nodes is evaluated, as well as the impact of several physical layer impairments on the network performance. In amplified solutions, we show that L-band networks with 9 tributary nodes are feasible, being the optical signal-to-noise ratio achieved when considering amplifiers noise and fiber non-linear interference above 14 dB. In unamplified solutions, to fullfil the power budget, frequency reuse should be used between spans. We show that the in-band crosstalk caused by this frequency reuse leads to 1.5 dB power budget degradation, for a crosstalk level of -20 dB.